Implementasi Manajemen Kurikulum Dalam Meningkatkan Mutu Pendidikan - Taufik Rizki Sista (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
The aim of this research is to know (1) the curriculum management model in Vocational High School of Migas Cepu. (2) Quality education development in Vocational High School of Migas Cepu. (3) The supporting and a prohibitive factors in implementation of curriculum management and quality development in Vocational High School of Migas Cepu. (4) The curriculum management role in quality education development. This research is a field research by descriptive qualitative method. In collecting data, writer apply the field observation, deep interview to the related interviewees and another related resource. The research outcome is (1) the Vocational High School of Migas Cepu is a recommended school by government to apply the current curriculum of 2013, therefore the Vocational High School of Migas Cepu is combining the curriculum of KTSP and curriculum of 2013. (2) Planning, developing, applying, and evaluating curriculum held comprehensively according to curriculum’s demand. (3) The Vocational High School of Migas Cepu, pay their attention to developing quality of education, this is evidenced by the outcome target presence in national test that reach in 100% in last four years. The curriculum management control a 90% of school quality development, this is evidenced by applying many innovations and changing of learning model in school.